Role of satellite RNAs in cucumber mosaic virus-host plant interactions. A review - Kouadio, KT.; De Clerck, C.; Atcham Agneroh, T.; Parisi, O.; Lepoivre, P.; Jijakli, H. (Biotechnologie, Agronomie, Société et Environnement, 2013)
Subviral non-coding RNA molecules, known as satellite RNAs (satRNAs), are often associated with cucumber mosaic virus (CMV). These satRNAs require a helper virus (CMV in this case) for their replication, encapsidation and transmission. They modify CMV pathogenicity by either attenuating disease symptoms or by exacerbating them. This effect could be due either to competition between a helper virus and satRNAs for replication, or to specific satRNA sequences or secondary structures. The type of host plant and the CMV strain also affect the behavior of satRNAs. Recent studies have shown that satRNA replication is associated with the production of satRNA-derived small RNAs of 21-25 nucleotides in length, which play a key role in RNA silencing and could explain differences in CMV symptom severity. This review highlights the current understanding and recent advances in relation to satRNA-mediated disease symptoms in CMV-infected plants.